Situación actual de la obesidad en Ecuador - Morillo Aguirre, Elizabeth Alejandra (2020)
Obesity is considered a disease in which those who suffer from it can develop other types of diseases such as diabetes, hypertension and heart attack. In addition to psychological illnesses such as anxiety, depression, stress, frustration and fear. According to the latest report from the Organization for Economic Cooperation and Development (OECD 2017), it is estimated that in the world the country that leads the highest percentage of obesity is the United States, obtaining 38.2 percent of the entire population. In Ecuador, 70.18% obesity is registered in adults between 19 and 59 years of age in the province of Carchi. According to figures from the National Health and Nutrition Survey (ENSANUT 2018), data was collected in which the female gender has a higher rate of obesity with a percentage of 67.62. In addition, an additional problem of obesity is that it not only attacks adults, but also children and young people. In childhood obesity it is revealed that 35 out of 100 children are overweight and obese. This research shows the problems faced by people with obesity in the country, the causes and consequences that they could have on health. The current obesity situation at the international and national level is also analyzed through interviews, data and testimonies. The sources used in this research are general practitioners, nutritionists, psychologists, and testimonials from people suffering from obesity. This project seeks to provide alternative treatments for people suffering from this disease. Another objective is to identify how obesity is diagnosed and treated in Ecuador.